LIFE CYCLE, FOOD PLANTS, AND REPRODUCTIVE POTENTIAL IN CAPTIVITY OF Morpho menelaus occidentalis IN THE PERUVIAN AMAZON - VASQUEZ-BARDALES, Joel (2025)
We studied the oviposition preference, food plants, life cycle of Morpho menelaus occidentalis, and its natural enemies. Three butterfly gardens were constructed with host plants representative of the forest, previously confirmed as suitable for the species. Wild females were collected and introduced into the enclosures, where they were fed fermented ripe bananas. In these environments, oviposition by host species, the number of larvae, and the presence of natural enemies were recorded. In the natural forest, the plants consumed by adults were documented. The life cycle was evaluated under controlled laboratory conditions (24–30 °C, 86% relative humidity, and a photoperiod of 14L:10O) using 20 newly emerged larvae fed with Arachis pintoi. Growth, molting, and morphometry of each stage were recorded daily, and a Kaplan–Meier curve was constructed to estimate survival. Adults’ laid eggs most frequently on Vigna aff. candida, Platymiscium stipulare, and Piper aduncum, and consumed the juice of fermented fruits from eight plant species. The biological cycle had five larval stages and a total duration of 97.6 days, with a cumulative survival rate of nearly 80%, with the larval stage having the highest mortality rate. Two natural enemies were identified: an egg parasitoid wasp (Scelionidae), responsible for 47% of parasitism, and the ant Crematogaster sp., which preyed on 35% of the larvae. This study is the first complete characterization of the life cycle of M. m. occidentalis, evidencing its selective polyphagous behavior and highlighting the need for biosecurity and management measures for its breeding and conservation.